Perbedaan Populasi Nyamuk pada Kelembaban Udara di Taman Kota Surakarta - BACHELS J. S. A.; Sumardiyono .; Endang Sulaeman (Nexus Kedokteran Komunitas, 2012)
Background : Air humidity affects the age, the distance fly, and the speed multiplied, also the habits of biting and rest of mosquitoes. City parks give a habitat for breeding mosquitoes. The density of top vegetations and bottom vegetations of city parks affect the air humidity. In the good air humidity mosquitoes are more quickly multiplied and the period of life of mosquitoes are longer so that the population mosquitoes will increase. This research aimed to know whether there are population differences of mosquitoes between citiy parks with the good air humidity and not so good in the city of Surakarta. Methods : This research was observasional analytic. The objects of this research are 2 citiy parks in Surakarta who has been measured its air humidity, then were clasified in city parks with the good air humidity for the growth of mosquitoes and not so good for the growth of mosquitoes. The data were conducted at regular intervals every 9 days following the life cycle of mosquitos and lasted for 53 days in accordance with the term of the living of mosquitos. Independent t Test (sig. = 0.05) was used to find out the role of the variables. Results : The result of the Independent t Test was obtained significant (p) 0.034 (p < 0.05). It shows that the differences of significant average between air humidity good and not so good with the population of mosquitoes In the City Parks of Surakarta. Conclusion : Air humidity affect the population of mosquitoes in the City Parks of Surakarta. Keywords: Air humidity, mosquitoes, Citys parks